2020 IEEE International Electron Devices Meeting (IEDM) 2020
DOI: 10.1109/iedm13553.2020.9372075
|View full text |Cite
|
Sign up to set email alerts
|

Cryo-CMOS Interfaces for Large-Scale Quantum Computers

Abstract: Cryogenic CMOS (cryo-CMOS) is a viable technology for the control interface of the large-scale quantum computers able to address non-trivial problems. In this paper, we demonstrate state-of-the-art cryo-CMOS circuits and systems for such application and we discuss the challenges still to be faced on the path towards practical quantum computers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…In the case of CMOS sensors, another related challenge for deep-cryogenic operation is the usability of electronics in these devices at sub-Kelvin temperatures. The detailed properties of the electronics depend on target applications, and circuits designed to operate above 100 K may not perform well below 1 K. Numerous studies in the literature have been focusing on characterizing CMOS electronics designed for operation at around 4 K, and CMOS control and readout devices have been built to operate at these temperatures in quantum computing applications [41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58], or recently even as low as ∼ 0.05 K for use with quantum dots [59]. It would be instructive for the future experimental studies of the detector proposed in this paper to test simple CMOS circuits designed for operation at 4 K at the lower temperatures of the cold plate and the still flange.…”
Section: Jinst 18 P12005mentioning
confidence: 99%
“…In the case of CMOS sensors, another related challenge for deep-cryogenic operation is the usability of electronics in these devices at sub-Kelvin temperatures. The detailed properties of the electronics depend on target applications, and circuits designed to operate above 100 K may not perform well below 1 K. Numerous studies in the literature have been focusing on characterizing CMOS electronics designed for operation at around 4 K, and CMOS control and readout devices have been built to operate at these temperatures in quantum computing applications [41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58], or recently even as low as ∼ 0.05 K for use with quantum dots [59]. It would be instructive for the future experimental studies of the detector proposed in this paper to test simple CMOS circuits designed for operation at 4 K at the lower temperatures of the cold plate and the still flange.…”
Section: Jinst 18 P12005mentioning
confidence: 99%
“…This imposes a significant blockage to scaling up existing quantum computers, making it profoundly challenging, if not infeasible, to reach the targeted 10 3 qubits to 10 6 qubits range. To overcome this challenge, researchers have proposed moving the control circuits close to the qubits and operating them at cryogenic temperatures [4][5][6][7][8][9][10] . This will open the door for efficient data processing as well as rapidly carrying out the necessary classification to convert readout data to the digital world along with performing the required error corrections 4,5 .…”
Section: Introductionmentioning
confidence: 99%
“…Authors in [6] reported the use of 128 ×64 and 64 ×64 SRAM array at different layers in quantum error correction. Apart from error correction, memories are also required to store the intermediate signals to control and readout the qubits [22]- [24]. Since performance and power are of the utmost importance for this kind of data storage, memory technologies other than SRAM are not suitable to be used as storage elements.…”
Section: Introductionmentioning
confidence: 99%